2005
DOI: 10.1002/hep.20757
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor β can mediate apoptosis via the expression of TRAIL in human hepatoma cells

Abstract: Transforming growth factor ␤ (TGF-␤) has been shown to induce apoptotic cell death in normal and transformed hepatocytes. However, the exact mechanism through which TGF-␤ induces cell death is still unknown. We examined a potential role of various death receptor/ ligand systems in TGF-␤-induced apoptosis and identified the tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) as a mediator of TGF-␤-induced apoptosis in hepatoma cells. TGF-␤-induced apoptosis is significantly impaired upon blockage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…Our results clearly show a significant decrease of apoptosis of CEM cells upon coincubation with those hepatoma cells that were pretreated with siRNA for Smad4, JunD, or FosB before TGF-h stimulation, compared with Huh7 cells that were pretreated with control siRNA. Compromised TRAIL expression by silencing these signal transduction components correlates clearly to our previously published results, using TRAIL-R2-Fc to efficiently and specifically inhibit TGF-h -induced apoptosis in hepatoma cells (11). Therefore, TGF-h -induced TRAIL expression and function is dependent on functional expression of Smad4 as well as of the AP-1 components JunD and FosB.…”
Section: Silencing Of Ap-1 Components and Smad4 Severely Impairs Tgf-supporting
confidence: 88%
See 1 more Smart Citation
“…Our results clearly show a significant decrease of apoptosis of CEM cells upon coincubation with those hepatoma cells that were pretreated with siRNA for Smad4, JunD, or FosB before TGF-h stimulation, compared with Huh7 cells that were pretreated with control siRNA. Compromised TRAIL expression by silencing these signal transduction components correlates clearly to our previously published results, using TRAIL-R2-Fc to efficiently and specifically inhibit TGF-h -induced apoptosis in hepatoma cells (11). Therefore, TGF-h -induced TRAIL expression and function is dependent on functional expression of Smad4 as well as of the AP-1 components JunD and FosB.…”
Section: Silencing Of Ap-1 Components and Smad4 Severely Impairs Tgf-supporting
confidence: 88%
“…We previously examined a potential role of various death receptor/ligand systems in TGF-h -induced apoptosis and have identified the tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) as an important mediator of TGF-h -induced apoptosis in hepatoma cells (11). TRAIL belongs to a family of death ligand systems and has attracted attention for its ability to preferentially kill a wide variety of tumor cell lines (12,13), whereas most normal cells are resistant to TRAIL both in vitro and in vivo (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Although our data argue against a role for TRAIL in TGFh1-mediated NRP apoptosis, it remains possible that the human TRAIL receptorFc fusions we employed failed to block rat TRAIL signaling because of sequence differences between the human and rat TRAIL receptors. Consistent with this possibility, others have reported that human DR4-Fc inhibits TGFh1-induced apoptosis of human hepatoma cell lines (50).…”
Section: Discussionsupporting
confidence: 54%
“…TGFβ1 has demonstrated both growth-stimulatory and growth-suppressive functions depending on cellular context. [53][54][55] In contrast, we observed an approximately two-fold decrease in vascular endothelial growth factor (VEGF) RNA (Fig. 5C).…”
Section: Mammalian Cells With Reduced E1 Levels Show Altered Expressimentioning
confidence: 81%